2018
DOI: 10.1007/s00246-018-1922-8
|View full text |Cite
|
Sign up to set email alerts
|

Stent Angioplasty for Critical Native Aortic Coarctation in Three Infants: Up to 15-Year Follow-Up Without Surgical Intervention and Review of the Literature

Abstract: Management of neonatal native coarctation is debated till now. Surgical therapy remains an option but may be unwarranted in critically sick infants with complex lesions. Balloon dilatation has been employed but with early re-stenosis. Stent angioplasty has also been used but as a bridge towards definitive surgical therapy. Four critically sick infants with complex coarctation and additional co-morbidity factors underwent primary stent therapy as surgical intervention was denied. One patient had died earlier du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Especially in sick preterm and low birth weight infants, it seems reasonable to bridge the patient until surgery can be performed at a lower risk. While interventional balloon angioplasty has been described even in very small infants, some authors have also reported successful stent usage in pre‐ and postoperative aortic coarctation in infants . Typically, coronary bare metal stents with a target diameter of 3,5–4 mm were considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Especially in sick preterm and low birth weight infants, it seems reasonable to bridge the patient until surgery can be performed at a lower risk. While interventional balloon angioplasty has been described even in very small infants, some authors have also reported successful stent usage in pre‐ and postoperative aortic coarctation in infants . Typically, coronary bare metal stents with a target diameter of 3,5–4 mm were considered.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Echocardiographic evidence of significant restenosis and (C) impaired systolic left ventricular function after discontinuation of prostaglandin E1 infusion has been described even in very small infants, some authors have also reported successful stent usage in pre-and postoperative aortic coarctation in infants. 1,[7][8][9] Typically, coronary bare metal stents with a target diameter of 3,5-4 mm were considered. These stents are suitable for interventional redilation and have provided acceptable results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stenting of coarctation of the aorta (CoA) is well established in adults and children weighing more than 25 kg, but even in smaller children this technique is gaining acceptance [1,2]. In smaller children aged 3 months or more, ballooning is a treatment option for native and recurrent CoA [3], but there are recent reports of even smaller patients undergoing stent therapy as either a bridge to operation or as primary treatment [4][5][6][7][8][9]. Stenting of coarctations in small children has been carried out for several reasons in a limited number of patients [4][5][6][7][8]10].…”
Section: Introductionmentioning
confidence: 99%